Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - 1.3 Exercises: 60

Answer

$\lim\limits_{\Delta x \to 0}\dfrac{(x+\Delta x)^{2}-x^{2}}{\Delta x}=2x$

Work Step by Step

$\lim\limits_{\Delta x \to 0}\dfrac{(x+\Delta x)^{2}-x^{2}}{\Delta x}$ Applying direct substitution immediately will result in an indeterminate form. So first, evaluate $(x+\Delta x)^{2}$: $\lim\limits_{\Delta x \to 0}\dfrac{(x+\Delta x)^{2}-x^{2}}{\Delta x}=\lim\limits_{\Delta x \to 0}\dfrac{x^{2}+2x\Delta x+\Delta x^{2}-x^{2}}{\Delta x}=...$ $...=\lim\limits_{\Delta x \to 0}\dfrac{2x\Delta x+\Delta x^{2}}{\Delta x}=...$ Take out common factor $\Delta x$ in the numerator and simplify: $...=\lim\limits_{\Delta x \to 0}\dfrac{\Delta x(2x+\Delta x)}{\Delta x}=\lim\limits_{\Delta x \to 0}2x+\Delta x=...$ Now, apply direct substitution to evaluate the limit: $\lim\limits_{\Delta x \to 0}2x+\Delta x=2x+0=2x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.